Interaction with the inositol 1,4,5-trisphosphate receptor promotes Ca2+ sequestration in permeabilised insulin-secreting cells. - Islam, MS; Nilsson, T; Rorsman, P; Berggren, P (1991)
Electropermeabilised insulin-secreting RINm5F cells sequestered Ca2+, resulting in a steady-state level of the ambient free Ca2+ concentration corresponding to 723 +/- 127 nM (mean +/- SEM, n = 10), as monitored by a Ca(2+)-selective minielectrode. Inositol 1,4,5-trisphosphate (Ins(1,4,5)P3) promoted a rapid and pronounced release of Ca2+. This Ca2+ was resequestered and a new steady-state Ca2+ level was attained, which was always lower (460 +/- 102 nM, n = 10, P less than 0.001) than the steady-state Ca2+ level maintained before the addition of Ins(1,4,5)P3. Whereas the initial reuptake of Ca2+ subsequent to Ins(1,4,5)P3 stimulation was relatively slow, the later part of reuptake was fast as compared to the reuptake phases of a pulse addition of extraneous Ca2+. In the latter case the uptake of Ca2+ resulted in a steady-state level similar to that found in the absence of Ins(1,4,5)P3. Addition of Ins(1,4,5)P3 under this condition resulted in a further Ca2+ uptake and thus a lower steady-state Ca2+ level. Heparin, which binds to the Ins(1,4,5)P3 receptor, also lowered the steady-state free Ca2+ concentration. In contrast to Ins(1,4,5)P3, inositol 1,3,4,5-tetrakisphosphate was without effect on Ca2+ sequestration. These findings are consistent with the presence of a high-affinity Ins(1,4,5)P3 receptor promoting continuous release of Ca2+ under basal conditions and/or the Ins(1,4,5)P3 receptor being actively involved in Ca2+ sequestration.